Double Meniscal Ossicle, the First Description: CT and MRI Findings—Different Etiologies. (15th December 2015) - Kumar, Puneeth; Dey, Amit Kumar; Mittal, Kartik; Sharma, Rajaram; Hira, Priya
Abstract : We present a case of 2 ossicles in the medial meniscus with emphasis on MRI and CT findings. Meniscal ossicle is a rare entity and is quite uncommon on the medial side. By showing the typical signal characteristics and intrameniscal location, MRI can be helpful in distinguishing this from other more clinically significant abnormalities. It should be kept as differential from synovial chondromatosis or sesamoid bones like fabella as management is different for all of these entities.